A Jelly-Eating Hitchhiker in the Mediterranean: Molecular Identification of Brachyscelus rapacoides Stephensen 1925 (Amphipoda: Brachyscelidae) in Greece - Konstantinos Kalaentzis; Paraskevi Louizidou; Gerasimos Kondylatos; Elisavet Kaitetzidou; Lyndall Pereira da Conceicoa; Mara Lawniczak; Alex Makunin; Jack Monaghan; Paul Heath; Craig Corton; James Watts; Michelle Smith; et al. (Thalassas: An International Journal of Marine Sciences, 2026)
The hyperiid amphipod Brachyscelus rapacoides is a warm-water species associated with gelatinous zooplankton. In the Mediterranean it has been reported in association with Rhopilema nomadica in both Israel and Turkey. Here, we document the first record of B. rapacoides in Greek waters, representing the first confirmed record for Europe, based on both morphological examination and DNA barcoding of the mitochondrial COI gene. Specimens were collected from the umbrella of infested R. nomadica from two localities in the southeastern Aegean Sea. Diagnostic morphological characters, particularly the dentition of gnathopods 1–2 and male antennal morphology, agree with published redescriptions of the species. Phylogenetic analyses placed the studied specimens within B. rapacoides , clearly separated from congeners. This finding extends the known distribution of the species westwards in the Mediterranean and further supports its close ecological association with R. nomadica . The record highlights the role of gelatinous hosts in facilitating dispersal of symbiotic hyperiids and underscores the importance of integrating molecular tools and citizen science observations for early detection of overlooked pelagic associates.

Twenty-four-hour blood pressure and CSF biomarkers of Alzheimer’s disease and related dementias in a community cohort - Madeline Gibson; William T. O’Brien; Ella Rowsthorn; Katherine H. Franks; Lachlan Cribb; Marina Cavuoto; Beaudan Campbell-Brown; Ian Harding; Meng Law; Trevor T.-J. Chong; Stuart J. McDonald; Terence J. O’Brien; et al. (GeroScience, 2026)
Hypertension in midlife is associated with increased dementia risk, yet its relationship with early pathological changes of Alzheimer’s disease and related dementias (ADRD) remains unclear. Unlike office blood pressure (BP), 24-h ambulatory BP (ABPM) may better reflect cardiovascular risk, but associations between 24-h BP measures with ADRD biomarkers are unknown. This cross-sectional study examined associations between BP and cerebrospinal fluid biomarkers of ADRD in mid-to-late life. Dementia-free participants ( n = 77; mean age = 67 [SD, 6]; 39% women) from the community-based Brain and Cognitive Health (BACH) cohort underwent office and 24-h ABPM assessments to calculate mean BP, nocturnal dipping, blood pressure variability (BPV, coefficient of variation) across 24-h, awake and asleep periods. Participants also completed a lumbar puncture to assess ADRD biomarkers: Aβ42/Aβ40 ratio, phosphorylated tau at threonine 217 (pTau217), glial fibrillary acidic protein (GFAP), and neurofilament light chain (NfL). Linear regression models examined associations between BP and ADRD biomarkers, adjusting for age, sex, BMI, smoking, anti-hypertensive medication use, and APOE ε4 status. Higher 24-h and awake mean BP were associated with higher GFAP (24-h: per 1-SD unit increase, β = 1606.6 pg/mL, p = .03; awake: β = 1668.pg/mL, p = .03) and NfL (24-h: β = 172.3 pg/mL, p = .03; awake: β = 162.3 pg/mL, p = .04) levels. Elevated asleep BPV was associated with higher Aβ42/Aβ40 ratio ( β = 0.01, p = .01). No, other clear associations were identified for the other BP metrics ( p > .05 for all). Findings indicate that elevated BP is associated with neuronal injury and astrocytic reactivity, suggesting possible pathways through which BP may relate to neurodegenerative processes, independent of overt amyloid or tau.

Repeated barrier drown-out is required to facilitate long-distance migration of a potamodromous fish - Jason D. Thiem; Benjamin G. Fanson; David Ryan; Gavin L. Butler; David A. Crook; Doug J. Harding; Anthony Townsend; Ian J. Wooden; Ivor Stuart (Aquatic Sciences, 2025)
Migratory fish species are highly vulnerable to stream fragmentation. Potamodromous golden perch ( Macquaria ambigua ) inhabit the barrier-laden Murray–Darling Basin (MDB), Australia’s largest river system, and its lifecycle includes a requirement for uninterrupted stretches of flowing water habitat. Owing to these barriers, large-scale connectivity in many regions is limited to periods of high flow events that facilitate barrier drown-out. We undertook a 3-year (2021–2024) study using telemetry to quantify the movements of 150 adult golden perch from the Barwon–Darling River over a period that encompassed numerous high flow events and flooding. Approximately 75% of tagged golden perch undertook movements > 50 km, with > 90% of movements in an upstream direction, extending up to 1500 km and associated with increased river discharge. Tributary entries were detected on multiple occasions, with an apparent preference for specific tributaries. Ten fish migrated > 1000 km upstream across multiple flow events. The results of this study (1) highlight the importance of the Barwon–Darling River and tributaries as a key migration conduit for adult golden perch, (2) demonstrate that multiple flow events are required to achieve large-scale dispersal and (3) provide quantitative flow-movement relationships that can be used to support inter-regional management actions. These management actions might include barrier removal, the construction of fishways and protection of tributary–mainstem flow events.

Factor analysis of multimodal MRI, biofluid, and vascular biomarkers reveals latent constructs of brain health - Ella Rowsthorn; Ming Ann Sim; William T. O’Brien; Stuart J. McDonald; Katherine Franks; Benjamin Sinclair; Trevor T.-J. Chong; Stephanie Yiallourou; Marina Cavuoto; Lucy Vivash; Terence J. O’Brien; Xingfeng Shao; et al. (GeroScience, 2025)
Individual imaging and fluid biomarkers provide insights into specific components of brain health, but integrated multimodal approaches are necessary to capture the complex, interrelated biological systems that contribute to brain homeostasis and neurodegenerative disease. Using data from the Brain and Cognitive Health (BACH) cohort study ( N = 127; mean age = 67 years, 68% women), we performed an exploratory factor analysis to identify latent constructs of brain health. We included multimodal neurovascular imaging markers, brain atrophy metrics, plasma Alzheimer’s disease (AD) biomarkers, and cardiovascular risk factors. Five constructs emerged: “Brain & Vascular Health” (greater hippocampal volume, basal ganglia enlarged perivascular spaces (ePVS), cerebral blood flow, and HDL cholesterol; lower ventricle volume and BMI), “Structural Integrity” (greater cortical thickness, fractional anisotropy, and basal ganglia ePVS), “White Matter (WM) Fluid Dysregulation” (greater WM ePVS and Free Water), “AD Biomarkers” (higher phosphorylated tau [pTau]181 and pTau217; lower amyloid-beta 42/40 ratio), and “Neuronal Injury” (higher glial fibrillary acidic protein and neurofilament light chain). All constructs were associated with age (β = - 0.70–0.39, p ≤ 0.014), except for WM Fluid Dysregulation ( p > 0.05). Brain and Vascular Health and Structural Integrity (partial r = 0.305, p < 0.001) and AD biomarkers and neuronal injury (partial r = 0.248, p = 0.005) were positively correlated. Only Brain and Vascular Health was associated with global cognition (β = 0.27, SE = 0.13, p = 0.043). These findings provide a data-driven framework for examining distinct constructs underlying vascular health, fluid regulation, and neurodegenerative pathology. We demonstrate the utility of using multiple biomarkers to probe these biological systems, paving the way for future research to explore how these systems change across diverse neurodegenerative conditions. Graphical abstract

The Role of Verbal Fluency in the Cerebellar Cognitive Affective Syndrome Scale in Friedreich Ataxia - Louise A. Corben; Eliza Blomfield; Geneieve Tai; Hiba Bilal; Ian H. Harding; Nellie Georgiou-Karistianis; Martin B. Delatycki; Adam P. Vogel (The Cerebellum, 2024)
Cerebellar pathology engenders the disturbance of movement that characterizes Friedreich ataxia (FRDA), yet the impact of cerebellar pathology on cognition in FRDA remains unclear. Numerous studies have unequivocally demonstrated the role of the cerebellar pathology in disturbed cognitive, language and affective regulation, referred to as Cerebellar Cognitive Affective Syndrome (CCAS), and quantified by the CCAS-Scale (CCAS-S). The presence of dysarthria in many individuals with ataxia, particularly FRDA, may confound results on some items of the CCAS-S resulting in false-positive scores. This study explored the relationship between performance on the CCAS-S and clinical metrics of disease severity in 57 adults with FRDA. In addition, this study explored the relationship between measures of intelligibility and naturalness of speech and scores on the CCAS-S in a subgroup of 39 individuals with FRDA. We demonstrated a significant relationship between clinical metrics and performance on the CCAS-S. In addition, we confirmed the items that returned the greatest rate of failure were based on Verbal Fluency Tasks, revealing a significant relationship between these items and measures of speech. Measures of speech explained over half of the variance in the CCAS-S score suggesting the role of dysarthria in the performance on the CCAS-S is not clear. Further work is required prior to adopting the CCAS-S as a cognitive screening tool for individuals with FRDA.

Correction to: MR Imaging in Ataxias: Consensus Recommendations by the Ataxia Global Initiative Working Group on MRI Biomarkers - Gülin Öz; Sirio Cocozza; Pierre-Gilles Henry; Christophe Lenglet; Andreas Deistung; Jennifer Faber; Adam J. Schwarz; Dagmar Timmann; Koene R. A. Van Dijk; Ian H. Harding; Astrid Adarmes-Gómez; Andreas Thieme; et al. (The Cerebellum, 2023)

MR Imaging in Ataxias: Consensus Recommendations by the Ataxia Global Initiative Working Group on MRI Biomarkers - Gülin Öz; Sirio Cocozza; Pierre-Gilles Henry; Christophe Lenglet; Andreas Deistung; Jennifer Faber; Adam J. Schwarz; Dagmar Timmann; Koene R. A. Van Dijk; Ian H. Harding; Astrid Adarmes-Gomez; Andreas Thieme; et al. (The Cerebellum, 2023)
With many viable strategies in the therapeutic pipeline, upcoming clinical trials in hereditary and sporadic degenerative ataxias will benefit from non-invasive MRI biomarkers for patient stratification and the evaluation of therapies. The MRI Biomarkers Working Group of the Ataxia Global Initiative therefore devised guidelines to facilitate harmonized MRI data acquisition in clinical research and trials in ataxias. Recommendations are provided for a basic structural MRI protocol that can be used for clinical care and for an advanced multi-modal MRI protocol relevant for research and trial settings. The advanced protocol consists of modalities with demonstrated utility for tracking brain changes in degenerative ataxias and includes structural MRI, magnetic resonance spectroscopy, diffusion MRI, quantitative susceptibility mapping, and resting-state functional MRI. Acceptable ranges of acquisition parameters are provided to accommodate diverse scanner hardware in research and clinical contexts while maintaining a minimum standard of data quality. Important technical considerations in setting up an advanced multi-modal protocol are outlined, including the order of pulse sequences, and example software packages commonly used for data analysis are provided. Outcome measures most relevant for ataxias are highlighted with use cases from recent ataxia literature. Finally, to facilitate access to the recommendations by the ataxia clinical and research community, examples of datasets collected with the recommended parameters are provided and platform-specific protocols are shared via the Open Science Framework.

Fish and macroinvertebrate assemblages reveal extensive degradation of the world's rivers - Maria João Feio; Robert M. Hughes; Sónia R. Q. Serra; Susan J. Nichols; Ben J. Kefford; Mark Lintermans; Wayne Robinson; Oghenekaro N. Odume; Marcos Callisto; Diego R. Macedo; Jon S. Harding; Adam G. Yates; et al. (Global Change Biology, 2023)
Rivers suffer from multiple stressors acting simultaneously on their biota, but the consequences are poorly quantified at the global scale. We evaluated the biological condition of rivers globally, including the largest proportion of countries from the Global South published to date. We gathered macroinvertebrate‐ and fish‐based assessments from 72,275 and 37,676 sites, respectively, from 64 study regions across six continents and 45 nations. Because assessments were based on differing methods, different systems were consolidated into a 3‐class system: Good, Impaired, or Severely Impaired, following common guidelines. The proportion of sites in each class by study area was calculated and each region was assigned a Köppen‐Geiger climate type, Human Footprint score (addressing landscape alterations), Human Development Index (HDI) score (addressing social welfare), % rivers with good ambient water quality, % protected freshwater key biodiversity areas; and % of forest area net change rate. We found that 50% of macroinvertebrate sites and 42% of fish sites were in Good condition, whereas 21% and 29% were Severely Impaired, respectively. The poorest biological conditions occurred in Arid and Equatorial climates and the best conditions occurred in Snow climates. Severely Impaired conditions were associated (Pearson correlation coefficient) with higher HDI scores, poorer physico‐chemical water quality, and lower proportions of protected freshwater areas. Good biological conditions were associated with good water quality and increased forested areas. It is essential to implement statutory bioassessment programs in Asian, African, and South American countries, and continue them in Oceania, Europe, and North America. There is a need to invest in assessments based on fish, as there is less information globally and fish were strong indicators of degradation. Our study highlights a need to increase the extent and number of protected river catchments, preserve and restore natural forested areas in the catchments, treat wastewater discharges, and improve river connectivity.

Longitudinal investigation of brain activation during motor tasks in Friedreich ataxia: 24-month data from IMAGE-FRDA - Rosita Shishegar; Ian H. Harding; Louisa P. Selvadurai; Louise A. Corben; Martin B. Delatycki; Gary F. Egan; Nellie Georgiou-Karistianis (Brain Structure and Function, 2022)

Probing the effect of aroma compounds on the hydrodynamic properties of mucin glycoproteins - Vlad Dinu; Thomas MacCalman; Ni Yang; Gary G. Adams; Gleb E. Yakubov; Stephen E. Harding; Ian D. Fisk (European Biophysics Journal, 2020)
Aroma compounds are diverse low molecular weight organic molecules responsible for the flavour of food, medicines or cosmetics. Natural and artificial aroma compounds are manufactured and used by the industry to enhance the flavour and fragrance of products. While the low concentrations of aroma compounds present in food may leave no effect on the structural integrity of the mucosa, the effect of concentrated aroma volatiles is not well understood. At high concentrations, like those found in some flavoured products such as e-cigarettes, some aroma compounds are suggested to elicit a certain degree of change in the mucin glycoprotein network, depending on their functional group. These effects are particularly associated with carbonyl compounds such as aldehydes and ketones, but also phenols which may interact with mucin and other glycoproteins through other interaction mechanisms. This study demonstrates the formation of such interactions in vitro through the use of molecular hydrodynamics. Sedimentation velocity studies reveal that the strength of the carbonyl compound interaction is influenced by compound hydrophobicity, in which the more reactive short chain compounds show the largest increase in mucin-aroma sedimentation coefficients. By contrast, the presence of groups that increases the steric hindrance of the carbonyl group, such as ketones, produced a milder effect. The interaction effects were further demonstrated for hexanal using size exclusion chromatography light scattering (SEC-MALS) and intrinsic viscosity. In addition, phenolic aroma compounds were identified to reduce the sedimentation coefficient of mucin, which is consistent with interactions in the non-glycosylated mucin region.

Targeted Intravenous Nanoparticle Delivery: Role of Flow and Endothelial Glycocalyx Integrity - Ming J. Cheng; Ronodeep Mitra; Chinedu C. Okorafor; Alina A. Nersesyan; Ian C. Harding; Nandita N. Bal; Rajiv Kumar; Hanjoong Jo; Srinivas Sridhar; Eno E. Ebong (Annals of Biomedical Engineering, 2020)

Longitudinal Increases in Cerebral Brain Activation During Working Memory Performance in Friedreich Ataxia: 24-Month Data from IMAGE-FRDA - Rosita Shishegar; Ian H. Harding; Louise A. Corben; Martin B. Delatycki; Elsdon Storey; Gary F. Egan; Nellie Georgiou-Karistianis (The Cerebellum, 2020)

Tool Use by Four Species of Indo-Pacific Sea Urchins - Glyn A. Barrett; Dominic Revell; Lucy Harding; Ian Mills; Axelle Jorcin; Klaus M. Stiefel (Journal of Marine Science and Engineering, 2019)
We compared the covering behavior of four sea urchin species, Tripneustes gratilla, Pseudoboletia maculata, Toxopneustes pileolus, and Salmacis sphaeroides found in the waters of Malapascua Island, Cebu Province and Bolinao, Panagsinan Province, Philippines. Specifically, we measured the amount and type of covering material on each sea urchin, and in several cases, the recovery of debris material after stripping the animal of its cover. We found that Tripneustes gratilla and Salmacis sphaeroides have a higher affinity for plant material, especially seagrass, compared to Pseudoboletia maculata and Toxopneustes pileolus, which prefer to cover themselves with coral rubble and other calcified material. Only in Toxopneustes pileolus did we find a significant corresponding depth-dependent decrease in total cover area, confirming previous work that covering behavior serves as a protection mechanism against UV radiation. We found no dependence of particle size on either species or size of sea urchin, but we observed that larger sea urchins generally carried more and heavier debris. We observed a transport mechanism of debris onto the echinoid body surface utilizing a combination of tube feet and spines. We compare our results to previous studies, comment on the phylogeny of sea urchin covering behavior, and discuss the interpretation of this behavior as animal tool use.

Early Cretaceous palynostratigraphy of the Abu Tunis 1x borehole, northern Western Desert, Egypt, with emphasis on the possible palaeoclimatic effect upon the range of Dicheiropollis etruscus in North Africa - Amr S. Deaf; Ian C. Harding; John E.A. Marshall (Palynology, 2016)

Emplacement of the Cabezo María lamproite volcano (Miocene, SE Spain) - Thomas M. Gernon; Samuel Spence; Clive N. Trueman; Rex N. Taylor; Eelco Rohling; Stuart J. Hatter; Ian C. Harding (Bulletin of Volcanology, 2015)

Hans Gocht (1930–2014) - James B. Riding; Susanne Feist-Burkhardt; Robert A. Fensome; Ian C. Harding; Jörg Pross (Palynology, 2015)

Capital and income breeding: the role of food supply - Philip A. Stephens; Alasdair I. Houston; Karin C. Harding; Ian L. Boyd; John M. McNamara (Ecology, 2014)
An aspect of life history that has seen increasing attention in recent years is that of strategies for financing the costs of offspring production. These strategies are often described by a continuum ranging from capital breeding, in which costs are met purely from endogenous reserves, to income breeding, in which costs are met purely from concurrent intake. A variety of factors that might drive strategies toward a given point on the capital–income continuum has been reviewed, and assessed using analytical models. However, aspects of food supply, including seasonality and unpredictability, have often been cited as important drivers of capital and income breeding, but are difficult to assess using analytical models. Consequently, we used dynamic programming to assess the role of the food supply in shaping offspring provisioning strategies. Our model is parameterized for a pinniped (one taxon remarkable for the range of offspring‐provisioning strategies that it illustrates). We show that increased food availability, increased seasonality, and, to a lesser extent, increased unpredictability can all favor the emergence of capital breeding. In terms of the conversion of energy into offspring growth, the shorter periods of care associated with capital breeding are considerably more energetically efficient than income breeding, because shorter periods of care are associated with a higher ratio of energy put into offspring growth to energy spent on parent and offspring maintenance metabolism. Moreover, no clear costs are currently associated with capital accumulation in pinnipeds. This contrasts with general assumptions about endotherms, which suggest that income breeding will usually be preferred. Our model emphasizes the role of seasonally high abundances of food in enabling mothers to pursue an energetically efficient capital‐breeding strategy. We discuss the importance of offspring development for dictating strategies for financing offspring production.

Cretaceous (Albian–?early Santonian) palynology and stratigraphy of the Abu Tunis 1x borehole, northern Western Desert, Egypt - Amr S. Deaf; Ian C. Harding; John E. A. Marshall (Palynology, 2014)

Correction - Sijun Liu; Ian D. Bedford; Peter G. Markham; Morad Ghanim; Muhamad Zeidan; Henryk Czosnek; A. Bruyère; E. Herrbach; V. Brault; V. Ziegler-Graff; H. Guilley; J. F. J. M. Heuvel; et al. (Phytoparasitica, 1998)

Abstracts of presentations on plant protection issues at the xth international congress of virology - Sijun Liu; Ian D. Bedford; Peter G. Markham; Morad Ghanim; Muhamad Zeidan; Henryk Czosnek; A. Bruyère; E. Herrbach; V. Brault; V. Ziegler-Graff; H. Guilley; J. F. J. M. van den Heuvel; et al. (Phytoparasitica, 1998)

Abstracts of presentations on plant protection issues at the fifth international Mango Symposium Abstracts of presentations on plant protection issues at the Xth international congress of Virology - J. E. Peña; M. Wysoki; Gajendra Singh; Nancy Boscán de M.; Freddy J. Godoy; A. Obligado; C. J. Rossetto; I. J. A. Ribeiro; P. B. Gallo; N. B. Soares; J. C. Sabino; A. L. M. Martins; et al. (Phytoparasitica, 1997)